(3eTGcd eMGSHjI eYGUQI s - (3UGHQ(B, (3YHGSjs ((3GdLRGFQ(B:s (3GdfTQ GdLGeYj GdLOjO(B,s, 2021)
(3GdSjGSGJ GdeMGSHjI , GdJZjQGJ aj GdJbOjQGJ GdeMGSHjI hGdCNWGA, hGdeMGSHI Yf GdYbhO WhjdI GdCLd, heMGSHI GdehGQO GdHTQjI hCgejI QCS GdeGd GdacQj hGdGaUGM Yfg aj GdeDSSI GdGbJUGOjI, HGdGVGaI Gdi eMGSHI NSjd GdCehGd, heMGSHI GdeSDhdjI GdGLJeGYjI heMGSHI GdJVNe cPdc eMGSHI GdCOGA GdHjFj eY eaghe GdJcGdja GdHjFjI, HGdGVGaI Gdi eMGSHI GdbjeI GdYGOdI, heaghegG aj GdacQ GdeMGSHj , heMGSHI GdJbdHGJ aj CSYGQ UQa GdYedGJ GdCLfHjI, hCNjQG eYGjjQ GdeMGSHI hGdeQGLYI aj GdeDSSGJ GdeGdjI GdGSdGejI(B.s
(3eQGLY U(B.2015- 230s
Keywords: (3GdeMGSHIs